Away we go [videorecording (DVD)] - Mendes, Sam; Krasinski, John, 1979-; Rudolph, Maya; Daniels, Jeff, 1955-; Gyllenhaal, Maggie, 1977-; Janney, Allison; Messina, Chris; O'Hara, Catherine (Focus Features four-star collection, 2009)
Burt and Verona are a loving couple. Burt has always wanted to marry Verona, but Verona resists, not seeing the point of the institution. Regardless, they are having a baby together and question their potential parenting abilities. They decide to move closer to Burt's parents so they can share the experience with the baby's grandparents. In Verona's sixth month, she and Burt learn that his parents are moving to Belgium the month before the baby is due. Being mobile people, Burt and Verona decide to move. As they want to share their new family experience with people that they love, they decide to take a trans-continental trip to meet with old friends and relatives. Most of them are married with children of their own, and Burt and Verona want to see where they would like to live and with whom they want to share the experience.